STRATEGI PUBLIC RELATIONS STASIUN TELEVISI DALAM MEMBANGUN CORPORATE IMAGE (Studi Kasus Program Community Relations NET. Good People di Stasiun Televisi NET.) - Eggi Listy Bahatis Muthia (Universitas Mercu Buana, 2022)
NET television station. is a station that has a young age compared to other televisions in Indonesia, but is much loved by loyal viewers. Seeing the many loyal viewers of the television station, public relations creates a place to gather and exchange the views of loyal viewers of the NET television station. as the NET community. Good people. The purpose of this study was to find out the strategies carried out by the public relations television station NET. in building an image in the community.In this study using the public relations strategy theory Scoot M. Cutlip & Allen H. Center This study uses a constructivist paradigm with a qualitative approach to case study methods. Data collection techniques with interview techniques and observations and supported by literature studies. The results of this study are public relations television station NET. apply the Scoot M. Cutlip & Allen H.Center theory in implementing the public relations strategy. Besides that,